2014
DOI: 10.1186/1479-5876-12-205
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cystatin C biomarker for clinical measurement of renal disease by developed ELISA diagnostic kits

Abstract: BackgroundHuman cystatin C (HCC) is a potential biomarker for tubular damage and impaired renal function. It is difficult to obtain efficient paired monoclonal antibodies against HCC with low molecular to meet the requirements for clinical application The present study was to establish a stable and repeatable measurement for HCC with self-made monoclonal antibodies (McAbs) and Variable domain of heavy chain of heavy-chain antibody (VHHs) increase the sensitivity.MethodsWith hybridoma technology and phage displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In recent years, ELISA has been considered as the standard quantitative method for measurement of several proteins in diseases, such as cytokines [178], cathepsin L and K [179,180], and serum levels of cystatin C have clinical value in estimation of glomerulus filtration rate [181,182]. A commercially available human legumain ELISA-duokit (DY4769) from R&D Systems, containing a biotinylated legumain pAb for detection, was used to measure the total legumain concentrations in plasma or serum obtained from patients with carotid atherosclerosis, STEMI and CVD patients, healthy controls, and in conditioned media from primary cells and cell lines (paper I-III).…”
Section: Methods Used To Detect and Quantify Legumainmentioning
confidence: 99%
“…In recent years, ELISA has been considered as the standard quantitative method for measurement of several proteins in diseases, such as cytokines [178], cathepsin L and K [179,180], and serum levels of cystatin C have clinical value in estimation of glomerulus filtration rate [181,182]. A commercially available human legumain ELISA-duokit (DY4769) from R&D Systems, containing a biotinylated legumain pAb for detection, was used to measure the total legumain concentrations in plasma or serum obtained from patients with carotid atherosclerosis, STEMI and CVD patients, healthy controls, and in conditioned media from primary cells and cell lines (paper I-III).…”
Section: Methods Used To Detect and Quantify Legumainmentioning
confidence: 99%
“…SOD, catalase, MDA level of kidney tissue measured in UV-VIS Spectrophotometer by standard protocol [9,15,16]. IL-18 [17,18], KIM-1 [18,19], and cystatin-C [20] were measured by commercially available standard kit with standard protocol for kit literature by an ELISA plate reader.…”
Section: Biochemical Analysis By Semi Autoanalyzer Uv-vis Spectrophomentioning
confidence: 99%
“…Likewise, Cystatin-A and cystatin isoforms were reported in gingival crevicular fluid in periodontal patients and chicken egg white during embryogenesis, respectively [50,51]. It is suggested that salivary glands respond to inflammation stimuli to secrete more Cystatin-C into saliva [50] and it has been considered as a biomarker candidate of renal function [52]. Alterations of serum Cystatin C was considered as early marker for hyperthyroidism, cancer, renal function in diabetic patients, and cardiovascular diseases [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%